Description of the Interim Peculiarities of Mental Developmental and Learning Disturbances - Vīgante, Rasma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
More and more pupils with special needs, including those with learning disturbances and simple mental developmental disturbances, are attending general comprehensive educational institution. It is often difficult in practice to define clearly and differentiate these two kinds of disturbances, especially in borderline cases or in the interim stage because then the features and manifestations of learning disturbances and simple mental developmental disturbances partly overlap and change. The novelty of the article is the analysis of the interim peculiarities and manifestations of these two disturbances which will allow teachers to understand better the main learning difficulties of such pupils and to choose the corresponding kinds of pedagogical support and methods as well as the correction and compensation possibilities.